Extreme turbulence in the media in 2011 - Salaverría, Ramón (Anuario ThinkEPI, 2012)
Review of developments, changes and trends in radio, television, and online and print media in 2011. The strong impact of the economic crisis is discussed: unfortunately many newspapers have had to reduce staff, and a large number of journalists have been dismissed. The consequences of the general transition from paper to digital, and the new internet developments that day by day gain more audience and attract advertising are described. Statistics are provided.